Rural housing in India - Raj, K.N. (1996)
Evaluating the rural housing scenario obtaining in the country, the author underscores the need for giving higher priority to rural housing and extension of essential facilities to such housing. Even the financial allocations made for them had not been adequately utilized. Nor has enough attention been given to reducing construction cost. Calling for the active involvement of NGOs in building rural houses, the author cautions against the hostility of vested interests to cost-effective technologies. - Reproduced
Keywords: Non governmental organizations - India; Housing - India; Housing